The Analysis of the Exact Solutions of the Space Fractional Coupled KD Equations - Demiray, Seyma Tuluce; Pandir, Yusuf; Bulut, Hasan (Amer Inst Physics, 2015)
In this study, we seek exact solutions of the space fractional coupled Konopelchenko-Dubrovsky (KD) equations by using generalized Kudryashov method. The space fractional coupled KD equations can be converted into nonlinear ordinary differantial equation by transformation. Consequently, generalized Kudryashov method has been used to obtain exact solutions of the space fractional coupled KD equations. From hence, we find some new hyperbolic function solutions. Also, we emphasize that this method is a generalized form of classical Kudryashov Method.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 22-28, 2014 -- Rhodes, GREECE
Keywords: The Space Fractional Coupled KD Equations; Generalized Kudryashov Method; Hyperbolic Function Solutions